Suitability assessment for forest landscape restoration based on species diversity conservation - Fan, Niqiao; Wang, Yiwen; Yang, Xin; Li, Jiajing; Kang, Jiemin; Liu, Qiang; Zhang, Zhidong (Frontiers in Forests and Global Change, 2024)
Forest landscape fragmentation poses a significant challenge to the conservation of species diversity. Evaluating the suitability of forest landscape restoration (FLR) becomes essential as it promotes effective management of forest resources and protects species diversity. This study focused on deploying and testing a suitability evaluation framework system for FLR in the Saihanba area of Hebei, China. The framework system incorporated factors such as land cover type, landscape structure, soil quality, and topography. Using the matter-element model, the study evaluated the restoration suitability and identified priority restoration areas. The results revealed that land cover type and landscape structure were the primary factors influencing FLR in the study area. The suitable area for FLR in the study area was about 519.20 km² , accounting for 55.55% of the total area. The area of moderate, marginal, and unsuitable restoration accounted for 17.30%, 23.96%, and 3.18% of the study area, respectively. The suitable restoration areas predominantly consisted of natural secondary forest characterized by large patch areas, short distances between patches, and complex patch shapes. In the study area, the objective of FLR should be protect large and complex shaped patches of natural secondary forests for better conservation of species diversity. The FLR suitability evaluation conducted in this study provide a valuable guidance for promoting species-diversity conservation and restoration of forest ecosystems at the landscape scale in the study area and other similar regions.